Study on a Coconut Shell as an Additive in a Concrete MIx - Sharifah Nur Athirah Binti Wan Abiddin,; Norfaniza Binti Mokhtar, (Recent Trends in Civil Engineering and Built Environment, 2022)
Due to struggling with the issue of rising solid waste disposal, with industrial waste being one of them including agricultural waste. Many researches have now been performed on the use of natural waste as an additive in concrete mixtures. The coconut shell is one of the solid wastes from agricultural disposal operation. The focus of this study is to evaluate the effectiveness of the coconut shell as an additive in the concrete mixture and to observe the influence of the coconut shell inclusion in concrete on the microstructural characteristics. By critical review from previous research with the relevant facts of the concrete with a coconut shell as an additive. From the analysis, it shows that 20 percent are the most suitable percentage to added the coconut shell as an additive. Due to the suitable compressive strength along with the tensile strength by given 24.22 MPa and 2.77 MPa respectively. It also influences the water absorption results. In addition, in microstructural testing, performed a Scanning Electron Microscope (SEM), X-ray Diffractometer (XRD) and Fourier Transform Infra-red (FTIR). SEM shows that the coconut shell soaked with water has a high in water absorption and XRD results shows that the sample is not containing a radioactive material. Lastly under FTIR testing, the sample shows that it contains quartz, carbon and vitreous phase. To conclude coconut shell is suitable to be added as an additive in the concrete.